Does this lung nodule need urgent review? A discrete choice experiment of Australian general practitioners - P. Brownell; F. Piccolo; F. Brims; R. Norman; D. Manners (BMC Pulmonary Medicine, 2020)
Abstract Background Lung cancer is the leading cause of cancer mortality in Australia. Guidelines suggest that patients with suspected lung cancer on thoracic imaging be referred for urgent specialist review. However, the term “suspected” is broad and includes the common finding of lung nodules, which often require periodic surveillance rather than urgent invasive investigation. The British Thoracic Society recommends that a lung nodule with a PanCan risk > 10% be considered for invasive investigation. This study aimed to assess which factors influence general practitioners (GPs) to request urgent review for a lung nodule and if these factors concur with PanCan risk prediction model variables. Methods A discrete choice experiment was developed that produced 32 individual case vignettes. Each vignette contained eight variables, four of which form the parsimonious PanCan risk prediction model. Two additional vignettes were created that addressed haemoptysis with a normal chest computed tomography (CT) scan and isolated mediastinal lymphadenopathy. The survey was distributed to 4160 randomly selected Australian GPs and they were asked if the patients in the vignettes required urgent (less than two weeks) specialist review. Multivariate logistic regression identified factors associated with request for urgent review. Results Completed surveys were received from 3.7% of participants, providing 152 surveys (1216 case vignettes) for analysis. The factors associated with request for urgent review were nodule spiculation (adj-OR 5.57, 95% CI 3.88–7.99, p < 0.0001), larger nodule size, presentation with haemoptysis (adj-OR 4.79, 95% CI 3.05–7.52, p < 0.0001) or weight loss (adj-OR 4.87, 95% CI 3.13–7.59, p < 0.0001), recommendation for urgent review by the reporting radiologist (adj-OR 4.68, 95% CI 2.86–7.65, p < 0.0001) and female GP gender (adj-OR 1.87, 95% CI 1.36–2.56, p 0.0001). In low risk lung nodules (PanCan risk < 10%), there was significant variability in perceived sense of urgency. Most GPs (83%) felt that a patient with haemoptysis and a normal chest CT scan did not require urgent specialist review but that a patient with isolated mediastinal lymphadenopathy did (75%). Conclusion Future lung cancer investigation pathways may benefit from the addition of a risk prediction m9odel to reduce variations in referral behavior for low risk lung nodules.